Soul sea waters - Salles, Laurita Ricardo de; Pereira, Leonardo Meneses (DAT Journal, 2021)
This article presents the reflections of the artist researchers who authored the video work Águas de al-mar, for the PANORAMA EXPO exhibition at LABLUZ, a panoramic and sound device located in the Josep Renau showroom of the Faculty of Fine Arts of the Polytechnic University of Valencia, Spain, presented to the public in June 2021 at the VIII SIIMI/International Seminar on Innovation in Interactive Media, #20 ART and 8th Balance-Unbalance. The piece presents a succession of vid- eo clips of the waters of Rio Grande do Norte, in a cinematic flow and metaphorical sound as emotions of the soul. The work is linked to the notions of expanded cinema and exhibition cinema, and is thought of in terms of their relationship with the cut, framing and scene in the audiovisual and with the options defined for the montage of the work, taking advantage of the horizontal frame cutout of the panoramic screen,among other issues.